2014
DOI: 10.1007/s00404-014-3175-y
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of obstetric outcomes in electively or spontaneously reduced triplet pregnancies

Abstract: Obstetric outcomes of triplets from IVF or ovulation induction cycles undergoing elective reduction are better than ongoing triplet and spontaneous reduction groups and are similar to that of dichorionic twins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…Sixty-six full-text articles were excluded for the following reasons: no control group (n = 35); comparison group of non-reduced twins (n = 22), and chorionicity other than trichorionic-triamniotic (n = 9). Among the accepted 26 articles two studies were found (Papageorghiou et al, 2002;Sebire et al, 1997) reporting data that were included in a more recent study (Papageorghiou et al, 2006), thus the latter study was considered only for data synthesis, leaving a total of 24 articles (Table 1) that met the final inclusion criteria (Angel et al, 1999;Antsaklis et al, 2004;Ata et al, 2011;Bergh et al, 1999;Bollen et al, 1993;Boulot et al, 2000;Chaveeva et al, 2013;Drugan et al, 2013;Geipel et al, 2004;Kadhel et al, 1998;Leondires et al, 2000;Lipitz et al, 1994;Macones et al, 1993;Okyay et al, 2014;Papageorghiou et al, 2006;Porreco et al, 1991;Raval et al, 2015;Shiva et al, 2014;Sivan et al, 2002;Skiadas et al, 2011;Smith-Levitin et al, 1996;van de Mheen et al, 2014;Yaron et al, 1999;Zhang et al, 2003). The agreement between the independent reviewers on study inclusion was considered good (Kappa = 0.88).…”
Section: Search Resultsmentioning
confidence: 99%
“…Sixty-six full-text articles were excluded for the following reasons: no control group (n = 35); comparison group of non-reduced twins (n = 22), and chorionicity other than trichorionic-triamniotic (n = 9). Among the accepted 26 articles two studies were found (Papageorghiou et al, 2002;Sebire et al, 1997) reporting data that were included in a more recent study (Papageorghiou et al, 2006), thus the latter study was considered only for data synthesis, leaving a total of 24 articles (Table 1) that met the final inclusion criteria (Angel et al, 1999;Antsaklis et al, 2004;Ata et al, 2011;Bergh et al, 1999;Bollen et al, 1993;Boulot et al, 2000;Chaveeva et al, 2013;Drugan et al, 2013;Geipel et al, 2004;Kadhel et al, 1998;Leondires et al, 2000;Lipitz et al, 1994;Macones et al, 1993;Okyay et al, 2014;Papageorghiou et al, 2006;Porreco et al, 1991;Raval et al, 2015;Shiva et al, 2014;Sivan et al, 2002;Skiadas et al, 2011;Smith-Levitin et al, 1996;van de Mheen et al, 2014;Yaron et al, 1999;Zhang et al, 2003). The agreement between the independent reviewers on study inclusion was considered good (Kappa = 0.88).…”
Section: Search Resultsmentioning
confidence: 99%
“…Sixty-nine full-text articles were excluded for the following reasons: no control group (n = 43); comparison group other than non-reduced twins (n = 19); reported chorionicity other than trichorionic-triamniotic (n = 7). Twenty-two cohort studies (Table 1) met the final inclusion criteria (Alexander et al, 1995;Angel et al, 1999;Antsaklis et al, 1999;Ata et al, 2011;Brambati et al, 2004;Cheang et al, 2007;Depp et al, 1996;Donner et al, 1992;Groutz et al, 1996;Haas et al, 2014;Hershko-Klement et al, 2013;Iberico et al, 2000;Lipitz et al, 1996;Macones et al, 1993;Mansour et al, 1999;Nevo et al, 2003;Okyay et al, 2014;Selam et al, 1999;Smith-Levitin et al, 1996;Torok et al, 1998;van de Mheen et al, 2014;Yaron et al, 1999). We could not identify any overlapping databases among the accepted articles.…”
Section: Search Resultsmentioning
confidence: 99%
“…When counselling prior to MPR, a major difficulty is the lack of clarity with regards to the outcome of twin pregnancies following reduction compared with that of non-reduced twin pregnancies. While some studies found no difference in either gestational age or mean birthweight between the groups (Haas et al, 2014;Hershko-Klement et al, 2013;Okyay et al, 2014), others did find a benefit for the nonreduced twins (Cheang et al, 2007;van de Mheen et al, 2014). One study even reported an advantage for the MPR group over the nonreduced twins with regards to gestational age and birthweight at delivery (Yaron et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…After correction for study heterogeneity, the estimated GDM prevalence was 7.3% (95% CI: 5.0-9.9) for the analysis of all 38 eligible studies [9, (Figure 2) with an I 2 of 93.2% for total study heterogeneity. The estimated GDM prevalence was 12.4% (95% CI: 6.9-19.1), when only studies with a sound GDM definition were used [9,33,37,41,43,48,52,53,55,59] with an I 2 of 83.2% (Figure 3). Table 3 provides an overview on the GDM definitions used and other study characteristics in the second meta-analysis.…”
Section: Meta-analysismentioning
confidence: 99%